Empowering Women HR in Construction Projects in Indonesia - Yeti Rohayati; Jufri Jacob; B.M.A.S. Anaconda Bangkara; Diani Indah; Indriyati Kamil (Budapest International Research and Critics University, 2022)
Usually, the human resources in the construction world in Indonesia are in demand by men, even though the job opportunities between men and women are not that different. However, the reality is that women's resources in construction are still very few presentations. This study attempts to discuss the empowerment of women's resources in construction projects and the constraints and problems women face in construction work. To support this discussion, we conducted an electronic search for data on published literature both nationally and internationally. After the data was collected, we conducted an in-depth study under a phenomenological approach, namely an effort to find answers from several existing data. Based on the study and discussion results, we can conclude that empowering women's human resources in construction projects is a government priority stated in the employment law. However, more and more women are slowly found in construction projects with all their advantages and disadvantages. Thus, the results of this study are the basis of guidance for further studies.